An object-based analysis of lightning characteristics in pre-tropical cyclogenesis environments - Mesa, Nicholas A., author; Bell, Michael M., advisor; Rasmussen, Kristen L., committee member; van de Lindt, John, committee member (Colorado State University. Libraries, 2025)
The Geostationary Lightning Mapper (GLM) on GOES-16 provides continuous, high-resolution data that enables a novel investigation of lightning attributes in pre-tropical cyclogenesis environments. An object-based framework, which provides additional spatiotemporal characteristics, was used to evaluate the area and optical energy of GLM lightning groups through the Tracking and Object-Based Analysis of Clouds (tobac) Python package. Applying tobac's compositing and tracking methods to GLM observations was first tested with a case of genesis (Tropical Storm Claudette (2021)) within range of the NEXRAD network. Collocated ground-based, dual-polarization radar observations suggested that small-area and low-energy lightning was indicative of stronger convection and updrafts via composite vertical radar profiles of tobac lightning features. The physical interpretations of these lightning attributes were then applied to lightning 72 hours prior to genesis and within 200 km of the best-track invest center for four developing disturbances (Claudette (2021), Ida (2021), Earl (2022), and Beryl (2024)). The presence of small-area and low-energy lightning, previously associated with stronger updrafts and convection, was seen at various times prior to genesis for all cases. Large-area and high-energy lightning was also identified for all cases at various times in the analysis period. Lightning was suggested to be modulated by deep-layer vertical wind shear, and multiple instances of electrified convection were noted to coincide with improvements in organization. More work is needed to evaluate these lightning attributes in a larger composite of pre-genesis disturbances. This work offers a novel characterization of oceanic lightning in pre-tropical cyclogenesis environments for the North Atlantic basin.
Keywords: object-based tracking; tropical cyclone; tropical cyclogenesis; lightning